Efficacy of recombinant thrombomodulin for poor prognostic cases of acute exacerbation in idiopathic interstitial pneumonia: secondary analysis of the SETUP trial. Issue 1 (17th May 2020) - Arai, Toru; Kida, Hiroshi; Ogata, Yoshitaka; Marumo, Satoshi; Matsuoka, Hiroto; Gohma, Iwao; Yamamoto, Suguru; Mori, Masahide; Sugimoto, Chikatoshi; Tachibana, Kazunobu; Akira, Masanori; Inoue, Yoshikazu
Abstract : Background: Acute exacerbation (AE) in idiopathic pulmonary fibrosis and other idiopathic interstitial pneumonias (IIPs) are poor prognostic events although they are usually treated with conventional therapy with corticosteroids and immunosuppressants. Previously, we demonstrated the safety and efficacy of recombinant human soluble thrombomodulin (rhTM) for AE-IIP in the SETUP trial. Here, we aimed to clarify the efficacy of rhTM for poor-prognosis cases of AE-IIP. Methods: In this study, we included 85 patients, in whom fibrin degradation product (FDP)/d-dimer was evaluated at AE, from the 100 patients in the SETUP trial. The AE-IIP patients in the rhTM arm (n=39) were diagnosed using the Japanese criteria from 2014 to 2016 and treated with intravenous rhTM for 6 days in addition to the conventional therapy. The AE-IIP patients in the control arm (n=46) were treated with the conventional therapy without rhTM between 2011 and 2013. The subjects were classified into higher and lower FDP/d-dimer groups based on the Japanese Association for Acute Medicine Disseminated Intravascular Coagulation scoring system. A multivariate Cox proportional hazard regression analysis with stepwise selection was performed to reveal the prognostic factors of AE-IIP. Results: We developed a prognostic scoring system using two significant prognostic factors, higher FDP/d-dimer at AE and prednisolone therapy before AE, with 3 and 2 points assigned for each parameter, respectively. The prognostic scores ranged from 0 to 5. Survival of AE-IIP patients with a prognostic score=0 was significantly better than that of patients with score ≥2. Survival was improved with the rhTM therapy (p<0.05) in the poor prognostic cases (score ≥2), but not in the good prognostic cases (score=0). Conclusions: Treatment with rhTM might improve survival in AE-IIP cases with poor prognoses. Trial registration number UMIN000014969, date: 28 August 2014.